New methods for the calibration of optical resonators: integrated calibration by means of optical modulation (ICOM) and narrow-band cavity ring-down (NB-CRD) - Finkenzeller, Henning; Pöhler, Denis; Horbanski, Martin; Lampel, Johannes; Platt, Ulrich (Atmospheric measurement techniques, 2023)
Optical resonators are used in spectroscopic measurements of atmospheric trace gases to establish long optical path lengths L with enhanced absorption in compact instruments. In cavity-enhanced broad-band methods, the exact knowledge of both the magnitude of L and its spectral dependency on the wavelength λ is fundamental for the correct retrieval of trace gas concentrations. L(λ) is connected to the spectral mirror reflectivity R(λ), which is often referred to instead. L(λ) is also influenced by other quantities like broad-band absorbers or alignment of the optical resonator. The established calibration techniques to determine L(λ), e.g. introducing gases with known optical properties or measuring the ring-down time, all have limitations: limited spectral resolution, insufficient absolute accuracy and precision, inconvenience for field deployment, or high cost of implementation. Here, we present two new methods that aim to overcome these limitations ...
Gesehen am 19.12.2023